Utility of cell-free transrenal DNA for the diagnosis of Tuberculous Meningitis: A proof-of-concept study. (July 2022) - Dass, Manisha; Aittan, Simran; Muthumohan, Rajagopalan; Anthwal, Divya; Gupta, Rakesh Kumar; Mahajan, Gargi; Kumari, Pooja; Sharma, Neera; Taneja, Rajesh S.; Sharma, Lokesh Kumar; Shree, Ritu; Lal, Vivek; et al.
Abstract: Tuberculous Meningitis (TBM) diagnosis remains a grave challenge. We evaluated the utility of extracellular vesicles (EVs) as a source of cell-free transrenal-mycobacterial DNA (cf-Tr-MTB DNA) for TBM diagnosis from urine samples. We developed a qPCR-assay targeting a highly repetitive 36-bp sequence specific to Mycobacterium tuberculosis complex. EVs were isolated from urine samples of suspected TBM groups (n = 44) [categorized using composite reference standard as 'Definite' TBM (n = 8), 'Probable' TBM (n = 15), 'Possible' TBM (n = 21)] and 'Non-TBM' group (n = 26). cf-Tr-MTB DNA-based qPCR assay was applied to DNA isolated from EVs (EV-DNA) and EV-free-fraction (EV-free DNA). ROC-curves were generated using qPCR results of 'Definite' TBM and 'Non-TBM' category in both EV-DNA and EV-free DNA samples and cut-off values were selected to provide 100% (95%CI:69.1–100) specificity. The cf-Tr-MTB DNA assay gave a sensitivity of 54.5% (95%CI:38.8–69.6) for EV-DNA and 77.3% (95%CI:62.1–88.5) for EV-free DNA in the TBM group (n = 44). The combination of EV-DNA and EV-free DNA results (corresponding to performance cf-Tr MTB DNA assay in urine), gave an overall sensitivity of 81.8% (95%CI:67.2–91.8) in the TBM group. Our results confirmed EVs as one of the sources of cf-Tr-MTB DNA and we believe the cf-Tr-MTB DNA-based qPCR assay has a potential application for TBM diagnosis.